Protective Resistance by Human G6PD Enzyme Deficiency and Hemoglobin Variants Against Malaria and Natural Selection: Further Evidence from Review of New Studies - RS, Balgir (Edelweiss Applied Science and Technology, 2019)
Main objective of this article is to review and evaluate recent red cell variant studies for protection against malaria and natural selection. Malaria is a parasitic disease highly widespread in tropical and subtropical regions of the world. It is also one of the leading causes of death worldwide and genes involved in malaria resistance are the most important for natural selection in human populations. Multiple red cell variants, which evolved probably to counter the lethal effects of malaria and confer protection against malaria through different mechanisms, show high frequencies in malaria endemic vulnerable populations. Different natural protective/resistance mechanisms including hampering of parasite growth, invasion related immunological responses or rapidly elimination of malaria parasite from the infected erythrocytes of host have briefly been discussed, evaluated, and reviewed. Conclusions drawn have been projected here. High frequency of inherited hemoglobin disorders including thalassemias, and red cell G6PD enzyme deficiency, which seemed to evolve simultaneously in relation to malaria, and high mortality caused by Plasmodium falciparum malaria in different vulnerable populations of tropical and subtropical parts of world, confirm that the natural selection is certainly operating against malaria in one way or another; and human population genetics have distinctly played a significant role in the co-evolution of host and malaria. The inverse relationship between sickle cell trait and G6PD deficiency and vice versa, revealed by allele frequencies distribution shown in our previous studies, is a testimony of disequilibrium, as sickle cell allele being replaced by G6PD deficiency allele in populations of central India. Positive natural selection plays a definite role against malaria for maintaining balance in high frequency endemic populations.